Sexual Harassment Experience, Gender Harassment and Body Objectification Effect on Disordered Eating Tendencies - Aleksė, Monika; Žardeckaitė-Matulaitienė, Kristina (Information & Media, 2021)
Various research on sexual harassment and gender harassment confirms the adverse effects on a person's physical and emotional health (Shrier, 1990), but so far, little is known about the impact of sexual harassment and gender harassment on one's body objectification and links to disordered eating behavior. Sexual harassment and gender harassment are not only based on gender stereotypes but also play an essential role in supporting gender norms in society by regulating what is seen as acceptable and unacceptable behavior, and appearance for gender. According to the theory of body objectification (Fredrickson, Roberts, 1997), both forms of gender discrimination can induce attention to one's body and appearance, which ultimately can lead to reduced satisfaction of one's body (Szymanski et al. 2011). Since body dissatisfaction is one of the leading causes of eating disorders (Brechan, Kvalem, 2015; Cruz-Sáez et al. 2018), it is important to have a better understanding of sexual harassment and gender harassment relationship with body objectification and disordered eating behavior. The study aims to assess the relationships between sexual harassment and gender harassment experiences, body-objectification, and disordered eating behavior tendencies. 181 (23 males, 158 females) aged 18-38 (M=24.12) participated in this research. Sexual Harassment Experience Questionnaire (Fitzgerald et al. 1998) was used to measure both Unwanted Sexual Attention (Cronbach α – 0,893) and Quid Pro Quo sexual harassment (Cronbach α – 0,876), and Gender Harassment experience (Cronbach α – 0,868). Objectified Body Consciousness Scale (McKinley et al. 1996) was used to measure body objectification: Body Shame (Cronbach α – 0,825) and Body Surveillance (Cronbach α – 0,804).  The Eating Attitudes Test (Garner et al. 1979) was used to evaluate disordered eating behavior tendencies: Dieting (Cronbach α – 0,924), Bulimia and Food Preoccupation (Cronbach α – 0,725) and Oral Control (Cronbach α – 0,714). The results revealed significant sexual harassment and gender harassment experience differences between genders showing that women report significantly higher results of all forms of sexual harassment and gender harassment than men. Data analysis also revealed a statistically significant relationship between higher results of sexual harassment, gender harassment experience, and more pronounced disordered eating tendencies and higher body objectification. Data analysis has shown that gender harassment experience is a significant prognostic factor for higher body surveillance and body shame results, more frequent dieting.
Keywords: sexual harassment; gender harassment; body objectification; disordered eating